2021
DOI: 10.3233/wor-213452
|View full text |Cite
|
Sign up to set email alerts
|

Repeated standing back extension exercise: Influence on muscle shear modulus change after lumbodorsal muscle fatigue

Abstract: BACKGROUND: In low back pain, multifidus muscle fibers reportedly exhibit increased stiffness. Low back pain was associated with lumbodorsal muscle fatigue. There is no report of using shear modulus to verify the mechanism of an immediate effect of exercise on low back pain. Here, temporary lumbodorsal muscle fatigue was created, simulating fatigue-related nonspecific low back pain. OBJECTIVE: To assess the effect of standing back extension exercise on fatigued lumbodorsal muscle based on the results of multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Indeed, studies examining lower limbs have shown, albeit not consistently for all muscles, a marked decrease in passive (during rest) and active (during contraction) shear modulus after isometric fatiguing protocol [ 26 , 27 , 28 ]. On the other hand, a possible increase has been noted for the passive shear modulus of the multifidus (MF) muscle [ 29 ]. Nevertheless, the effects of fatigue on trunk muscle stiffness should be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies examining lower limbs have shown, albeit not consistently for all muscles, a marked decrease in passive (during rest) and active (during contraction) shear modulus after isometric fatiguing protocol [ 26 , 27 , 28 ]. On the other hand, a possible increase has been noted for the passive shear modulus of the multifidus (MF) muscle [ 29 ]. Nevertheless, the effects of fatigue on trunk muscle stiffness should be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, performing the One Stretch exercise was reported to lead to improvements in circulatory dynamics of the erector spinae muscle and LBP symptoms. 32 The present LBP subject was instructed to slowly extend his back for 3 s and repeat the exercise one to two times a day after lifting something heavy and performing prolonged forward bending. We hypothesized that the exercise could improve his flexibility and alleviate his erector spinae muscle spasm symptoms.…”
Section: Case Reportmentioning
confidence: 99%
“…Exercise-induced muscle fatigue refers to the reduction in expected muscle strength and force output following repetitive muscle contractions caused by physical activity [20,23], which has been found to be closely associated with cLBP. Studies have reported that cLBP patients often experience exercise-induced muscle fatigue, and long-term sedentary posture or heavy work loading can contribute to the occurrence or recurrence of cLBP [24,25]. Recent studies suggest that postural control alteration may be a common characteristic of individuals with cLBP when faced with internal or external perturbation [26,27].…”
Section: Introductionmentioning
confidence: 99%